STUDY OF STATICALLY TESTED HONEYCOMB STRUCTURE - Sudirman Lubis; Ahmad Marabdi Siregar; Irpansyah Siregar (CERED Indonesia Institute, 2021)
Honeycomb structure is a natural or man-made structure (material) that has the geometry of the honeycomb, in addition to being directed to the mass of light construction material, also obtained a degree of flexibility from the selection of such materials. The purpose of this study is to analyze the ability of energy absorption in static press testing. Energy absorption is a method of how an object attenuated due to external pressure. Energy absorption testing is conducted with static press tests, aluminum plate test objects in the form of honeycomb structures with different hexagonal size variations. This test will compare the results of voltage data – strain and energy suppression in each specimen that has been tested to see which is more efficient among three specimens of different hexagonal sizes. The final results of this test will be displayed using a voltage graph – horizontal and vertical position strain and energy absorption capability with horizontal and vertical testing positions. Therefore, the largest energy absorption result is in the horizontal testing position with a hexagonal size of 2 mm, and the smallest energy absorption is found in the vertical testing position with a hexagonal size of 6 mm.